Phylogeographic analysis of Y-chromosomal haplogroup C2a-M48-F8472, a minor paternal lineage of Han populations with possible ancestry of Xiongnu - Xian-Peng Zhang; Hui-Xin Yu; Jin Sun; Hui Li; Kai-Jun Liu; Lan-Hai Wei (Taylor & Francis Group, 2024)
Background Y-chromosome haplogroup C2a-M48-F8472, a unique paternal line in the ancient Xiongnu population, is concentrated in the modern Han people. The most closely related lineage of this paternal lineage is mainly distributed in Tungusic-, Mongolic-, and Turkic-speaking populations.Aim To investigate the formation process of this unique distribution state.Subjects and methods In total, 36 sequences of haplogroup C2a-M48-F8472 were analysed to generate a revised phylogenetic tree with age estimation and to explore the geographic distribution pattern.Results The results suggested that northern China is likely the diffusion centre of this paternal haplogroup. This lineage is concentrated in the Liu clan (刘姓) of Han populations and may have originated in the Tuge tribe (屠各) of Xiongnu populations. The initial expansion (∼2,600 years ago) and the second phase of expansion (∼1,570 years ago) of haplogroup C2a-M48-F8472 coincide with the earlier appearance and later disappearance of the Tuge tribe. As a sub-clade of M48, the history of F8472 suggested that ancient peoples related to Tungusic-speaking populations were intricately connected with the demographic history of populations in the Mongolian Plateau.Conclusion The appearance of this paternal line in the Han population is helpful for understanding the mixed history of ancient and modern people in the Mongolian Plateau and Central China.